The Effect of Organizational Climate and Work Discipline on Organizational Commitment with Job Satisfaction as Mediation at the Palu City District Government Office - Melda Yanti; Purbudi Wahyuni; Heru Tri Sutiono (Journal of Business Innovation and Research, 2022)
This study aims to analyze the effect of organizational climate and work discipline on organizational commitment with job satisfaction as a mediating variable at the Government Office in Palu City District. This type of research is quantitative research. The population in this study amounted to 126 employees using the census technique. The data collection method in this study used a questionnaire measured by a Likert scale. The data analysis technique in this study uses Structural Equation Model (SEM) with Partial Least Square (PLS), SmartPLS 3.2.7 software. The results of this study indicate that organizational climate has a direct and significant positive effect on organizational commitment. Work discipline has a direct and significant positive effect on organizational commitment. Organizational climate has an indirect and significant positive effect on organizational commitment with job satisfaction as a mediating variable. Work discipline has an indirect positive effect on organizational commitment with job satisfaction as a mediating variable.